Anti-VEGF Therapy in Refractory Pituitary Adenomas and Pituitary Carcinomas: A Review - Dai, Congxin; Liang, Siyu; Sun, Bowen; Li, Yong; Kang, Jun (Frontiers in Oncology, 2021)
Most pituitary tumors are considered benign adenomas, and only 0.1-0.2% of them present metastasis and are defined as pituitary carcinomas (PCs). Refractory PAs lie between benign adenomas and true malignant PCs and are defined as aggressive-invasive PAs, characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments. It is notoriously difficult to manage refractory PAs and PCs because of the limited therapeutic options. Vascular endothelial growth factor (VEGF) plays a crucial role in angiogenesis not only during development but also during pathological processes in pituitary tumors. Recently, increasing numbers of preclinical studies and clinical research have demonstrated that anti-VEGF therapy plays an important role in pituitary tumors. The purpose of this review is to report the role of VEGF in the development and pathology of pituitary tumors and the progress of anti-VEGF therapy in pituitary tumors, including refractory PAs and PCs. Previous preclinical studies indicated that cyclin-dependent kinase 5 (CDK5)-mediated VEGF expression might play a crucial role in the development of PAs. Vascular endothelial growth inhibitors have been reported as independent predictors of invasion in human PAs and have been indicated as markers for poor outcome. Furthermore, several studies have reported that angiogenesis decreases tumor sizes in experimental animal models of pituitary tumors. The expression of VEGF is relatively high in PAs; therefore, anti-VEGF therapy has been used in some refractory PAs and PCs. To date, anti-VEGF has been reported as monotherapy, in combination with temozolomide (TMZ), TMZ and radiotherapy, and with pasireotide, which might be a promising alternative therapy for refractory PAs and PCs resistant to conventional treatments. However, the role of anti-VEGF therapy in pituitary tumors is still controversial due to a lack of large-scale clinical trials. In summary, the results from preclinical studies and clinical trials indicated that anti-VEGF therapy monotherapy or in combination with other treatments may be a promising alternative therapy for refractory PAs and PCs resistant to conventional treatments. More preclinical studies and clinical trials are needed to further evaluate the exact efficacy of anti-VEGF in refractory PAs and PCs.